2018
DOI: 10.1177/1082013218799027
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of essential oils against foodborne multidrug-resistant enterococci and aeromonads in planktonic and biofilm state

Abstract: The selection and use of natural compounds with antimicrobial activity against foodborne pathogens is of major importance. The present study evaluated the antimicrobial activity of commercial essential oils against multidrug-resistant Enterococcus spp. and Aeromonas spp. Cymbopogon flexuosus and Thymus vulgaris essential oils presented the highest inhibitory zones against both bacterial groups ( p < 0.05). Subsequent determination of the minimum inhibitory concentrations showed values between 0.47 and 1.9 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
(34 reference statements)
1
13
1
Order By: Relevance
“…25 Other options, such as pump inhibitors and essential oils, have been proved to have antibacterial activity against multidrug-resistant Enterococci in vitro. 26,27 Although previous studies showed 0.3% to 20% VRE were resistance to DAP, all isolates in our study were sensitive to DAP. 28,29 LNZ and DAP monotherapy showed effective anti-biofilm formation during 72 hours.…”
Section: Discussioncontrasting
confidence: 65%
“…25 Other options, such as pump inhibitors and essential oils, have been proved to have antibacterial activity against multidrug-resistant Enterococci in vitro. 26,27 Although previous studies showed 0.3% to 20% VRE were resistance to DAP, all isolates in our study were sensitive to DAP. 28,29 LNZ and DAP monotherapy showed effective anti-biofilm formation during 72 hours.…”
Section: Discussioncontrasting
confidence: 65%
“…In our research, among tested essential oils, TO showed the highest antibacterial activity against Aeromonas species, although the MIC values of TO were higher than TC. Quendera et al [36] also investigated antimicrobial activity of commercial TO against Aeromonas species and obtained MIC values were between 0.47 and 1.9 mg/mL. In our study, the MIC values of TO for most strains ranged from 0.39 to 0.78 mg/mL.…”
Section: Discussionsupporting
confidence: 55%
“…They are mixtures of aromatic compounds, including terpenes, terpenoids, phenols, and rakebones [9,10]. Essential oils, due to their huge biological activity, are used, among others, in the food industry as natural preservatives in order to reduce or eliminate the addition of preservative chemicals to foods such as cereals, grains, pulses, fruits, and vegetables [11,12].…”
Section: Introductionmentioning
confidence: 99%